Impact of Highly Effective Modulator Therapy on Olfactory‐Specific Gene Expression in People With Cystic Fibrosis - Michael R. Xiang; Ankit Chauhan; Gina Hong; Denis Hadjiliadis; Daniel Dorgan; Michael M. Rey; Samantha Kane; James N. Palmer; Nithin D. Adappa; Noam A. Cohen; Michael A. Kohanski; Jennifer E. Douglas (International Forum of Allergy & Rhinology, 2026)
ABSTRACT Background Chronic rhinosinusitis is common in people with cystic fibrosis (PwCF). Highly effective modulator therapy (HEMT) has been shown to improve sinonasal outcomes. However, prior studies failed to show improvement in objective olfaction with HEMT, and the impact of HEMT on olfactory‐specific quality of life has yet to be studied. Furthermore, the underlying changes in gene expression within the olfactory epithelium (OE) of PwCF remains poorly understood. Methods Single‐center cross‐sectional cohort study of PwCF. Patients with no history of cystic fibrosis (CF) or comorbid sinus disease were used as controls. Olfactory‐specific quality‐of‐life (QOD‐NS) and objective olfactory testing (Sniffin’ Sticks comprehensive test) were collected. Cytology brushings from the OE were obtained to isolate RNA for olfactory‐specific gene expression (OMP, TUJ1, KRT5, SOX2, OR9K2, and OR5AN1). Results Fifty PwCF were enrolled (HEMT n = 32, non‐HEMT n = 18, and control n = 17). A significant difference was found for QOD‐NS ( p = 0.041) but not for objective olfaction ( p = 0.72) by HEMT status. There was a significant difference between HEMT and non‐HEMT cohorts for SOX2 gene expression ( p = 0.016); there were no significant differences observed in other markers. Comparing PwCF to controls, significant differences were found in gene expression across all markers. Conclusion HEMT is associated with QOD‐NS but not objective olfaction in PwCF. HEMT may impact gene expression of support cells in the OE but does not appear to affect olfactory neuronal gene expression. This suggests PwCF have early and irreversible damage to the OE. Further studies are necessary to better understand CF‐induced changes to the OE.